PENGARUH PENGUMUMAN MERGER DAN AKUISISI TERHADAP RETURN SAHAM PERUSAHAAN AKUISITOR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005-2008 - Kurniawati, Rina; Setyono, Hendro (Universitas Ahmad Dahlan, 2011)
Purpose of this study to prove whether an announcements of mergers and acquisitions responded by market players so produce abnormal return for companies. This study also triying prove whether there abnormal return before and after an announcements of mergers and acquisitions.Data used in this study is companies conducting mergers and acquisitions listed at the Indonesia Stock Exchange period 2005-2008. Sample selection use purposive sampling. Samples obtained amount 11 company.From the analysis, use one sample T-Test obtained results calculation average abnormal return (AAR) shows that of overall average abnormal return (AAR) not found abnormal return significant. So can concluded that there is not differences abnormal return stock acquiring company about information an announcement of mergers and acquisitions announced acquiring company.Other findings in this study is test results by using uji t paired produce significant count is 0,007. Then hypothesis 2 this study able to prove. So it can be concluded that there significant differences abnormal return before and after an announcement of mergers and acquisitions.Limitations in this study is a limited number of samples caused still rare company that does mergers and acquisitions listed at the Indonesia Stock Exchange. Event window short only 21 days is 10 days before and 10 days after an announcement.